(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted at a coal mining company in Tanjung Enim, South Sumatra. This aim is to analyze the influence of organizational culture and transformational leadership style on job satisfaction to generate affective commitment based information technology. This method uses quantitative methods with a population of 140 employees and a sample of 111 and with data research techniques in the form of questionnaires and library data. Methods of data analysis using multiple regression analysis, validity test, reliability test, coefficient of determination, partial test with t-test. The results showed that organizational culture has a positive effect on job satisfaction with a significant value of 0.000 <0.05 and a β value of 0.457. Transformational leadership style has a positive effect on job satisfaction with a sig value of 0.000 <0.05 and a β value of 0.363.